Dynamic Evolution of Electric Vehicle Trade Network between China and Europe - Yan, Shigang; Liao, Zeng (European Scientific Journal, ESJ, 2025)
China and Europe have promoted the development of electric vehicles to reduce carbon emissions and cope with climate change. In recent years, the sales share of Chinese electric vehicle brands in the European market has increased rapidly. Europe has become the largest export market for Chinese electric vehicles. However, the European Union implemented various temporary tariffs on Chinese electric vehicle brands in 2024, which posed a major challenge to the development of electric vehicle trade between China and Europe. The paper conducts a systematic examination of overall structural characteristics, node centrality metrics, core-periphery architecture and community detection of electric vehicle trade network between China and Europe from 2018 to 2022 by using social network analysis. The results indicate a general upward trend in tighter trade groups and increased connectivity efficiency within the network, while the network density and reciprocity display some fluctuations during this period. From a structural perspective, countries holding central positions in both centrality measures and core-periphery indicators show statistically significant convergence patterns in electric vehicle trade network between China and Europe. Moreover, there has formed different communities and undergone significant composition changes in electric vehicle trade network after 2020, highlighting the strengthening of connectivity within the trade network. This study has both theoretical and practical implications. It highlights the dynamic changes in electric vehicle trade network between China and Europe, and providing practical implications for Chinese policymakers and Chinese electric vehicle manufacturers through strategic frameworks to enhance bilateral cooperation, market adaptability, and sustainable trade reciprocity with European countries.